A case study of public relations and marketing practices in the Rizal Provincial Library - Soliman, Andrei C.; Cabbab, Johann Frederick A. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2009)
Public libraries today are faced with a tough challenge of continuing to provide solutions to the information needs of people amid heavy competition. The competition arises from the ever increasing developments in technology like faster and more portable computers and readily available Internet access almost everywhere. The dwindling number of visitors in most public libraries in the Philippines is surely a matter of great concern and that is why librarians must be able to adapt to these different changes and use it for the benefit of the library and its clients.
Implementing public relations and marketing strategies is one if not the most effective means of ensuring that users will still patronize libraries. There are already a lot of modern practices that some libraries around the world have been using to stay in touch with clients and potential clients. The Internet for example could be used to keep clients informed of the different activities of a certain library.
This study focuses in the Rizal Provincial Library (RPL) - one of the libraries that surely feel the pressures of the changes that are occurring. It analyzes the different strategies that have been done and provides some other solutions on what can be done. The research instruments primarily used for this study are the questionnaires and an interview with the chief librarian of the RPL, Ms. Lucila G. Dela Vega.
The survey included 140 respondents. They were asked about their experiences in dealing with the library and also how they view the different marketing strategies that have been applied and what they think if new strategies that may be implemented. The researcher found out that the library does not have any formal marketing program in place. The results from the survey however, shows that it won't be a useless effort if the library takes such as an endeavor seriously as most respondents indicated that their interests will surely be boosted if the library will implement most of the programs cited in the survey. Recommendations were further provided to aid the library in case it decides to implement a formal marketing program.
Vita.
Thesis (Bachelor of Library and Information Science)
Keywords: Public relations -- Libraries -- Philippines -- Rizal